Vasopressin, oxytocin, dynorphin, enkephalin and corticotrophin-releasing factor mRNA stimulation in the rat. - Lightman, S L (1987)
1. Cryostat sections were cut through the hypothalamus of rats which had been given a 2% (w/v) NaCl solution to drink for up to 12 days. 2. In situ hybridization histochemistry was performed on these sections using synthetic oligonucleotide probes against part of the precursor sequence for vasopressin, oxytocin, dynorphin, enkephalin and corticotrophin-releasing factor (CRF). 3. Drinking 2% NaCl solution resulted in a progressive increase of vasopressin, oxytocin and dynorphin mRNAs hybridized in the magnocellular neurones of the supraoptic (s.o.) and paraventricular (p.v.) nuclei. No enkephalin mRNA was detected in the magnocellular areas of the control animals although small quantities of probe did hybridize after 12 days of salt loading and after the stress of I.P. hypertonic saline. 4. Ten-day-lactating female rats were also studied. They had a very marked increase in oxytocin mRNA with smaller increases of vasopressin and dynorphin mRNAs. No detectable enkephalin mRNA was hybridized in the magnocellular s.o. or p.v. nuclei and CRF mRNA was unchanged in both the s.o. nucleus and the p.v. nucleus.